PENDAMPINGAN PROGRAM ALIH TEKNOLOGI MESIN PEMOTONG SAYURAN UNTUK PENINGKATAN USAHA KUE TRADISIONAL YANG BERKUALITAS - Yovan Witanto; Hendra Hendra; Anizar Indriani (DHARMA RAFLESIA, 2020)
Pematang Gubernur, Muara Bangkahulu District, Bengkulu City, is a town where many people do small business making and selling traditional cakes or fried foods. This business uses vegetables, such as potato, carrot, cabbage   as base ingredients.  However, the people have not yet used technology to help them do the work, especially for the vegetable cutting process. Hence, they lack of time efficiency and consistency in size of the cut food. To overcome this, technology is needed in the form of a multipurpose vegetable cutting machine capable of cutting large capacity vegetables in no time. This community service activity aims to assist technology transfer programs to the community. The team of this program introduces the vegetable cutting machines, as well as providing and motivating ways to create, install and use vegetable cutting machines. Methods used in this program include assisting in the identification of vegetable / grass cutting machine components, design assistance, material selection and manufacturing of cutting machines and practice using cutting machines. The results show that participants are very interested in making and using the equipment. They expect the sustainability of this activity. Participants hope that this activity will be continued with training in making various forms of vegetable cutting mold. Different shapes of cutting is expected to get more attractive look of the food.